Performance analysis of robust road sign identification - Ali, Nursabillilah M; Mohd Mustafah, Yasir; Alang Md Rashid, Nahrul Khair (IOP Publishing, 2013)
This study describes performance analysis of a robust system for road sign identification that incorporated two stages of different algorithms. The proposed algorithms consist of HSV color filtering and PCA techniques respectively in detection and recognition stages. The proposed algorithms are able to detect the three standard types of colored images namely Red, Yellow and Blue. The hypothesis of the study is that road sign images can be used to detect and identify signs that are involved with the existence of occlusions and rotational changes. PCA is known as feature extraction technique that reduces dimensional size. The sign image can be easily recognized and identified by the PCA method as is has been used in many application areas. Based on the experimental result, it shows that the HSV is robust in road sign detection with minimum of 88 and 77 successful rate for non-partial and partial occlusions images. For successful recognition rates using PCA can be achieved in the range of 94-98. The occurrences of all classes are recognized successfully is between 5 and 10 level of occlusions.